PERANAN FILSAFAT ILMU TERHADAP PENGARUH PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - Wahlin Munte (Jurnal Genta Mulia, 2024)
The purpose of this article is to determine the role of philosophy of science on the influence of the development of science and technology (IPTEK). Technology and science which are increasingly popular are now attracting a lot of attention, especially among the millennial generation. Knowledge that develops according to the civilization of the times cannot be rejected or stopped temporarily, but can be responded to wisely. Society as participants in the development of science and technology must understand the importance of philosophy to create realistic and logical boundaries for the development of science so as not to harm humans, nature and the environment. The method used in this article is the library research method. The results of this article show that the philosophy of science needs to be present amidst the development of science and technology which is marked by increasingly sharp scientific specialization. The philosophy of science provides a vision for society, so that it does not remain silent under the influence of current developments. As members of society and especially the younger generation, we can take representative and proactive action to prevent as much as possible the negative impact of technology on life. The conclusion of this article is that the development of science and technology cannot be separated from the philosophy of science. The philosophy of science plays an important role in the development of science and technology at science and technology testing institutions to share critical and logical thinking on current developments in science and technology.